CtsR, the Master Regulator of Stress-Response in Oenococcus oeni, Is a Heat Sensor Interacting With ClpL1 - Darsonval, Maud; Julliat, Frédérique; Msadek, Tarek; Alexandre, Hervé; Grandvalet, Cosette (Frontiers in Microbiology, 2018)
Oenococcus oeni is a lactic acid bacterium responsible for malolactic fermentation of wine. While many stress response mechanisms implemented by O. oeni during wine adaptation have been described, little is known about their regulation. CtsR is the only regulator of stress response genes identified to date in O. oeni. Extensively characterized in Bacillus subtilis, the CtsR repressor is active as a dimer at 37°C and degraded at higher temperatures by a proteolytic mechanism involving two adapter proteins, McsA and McsB, together with the ClpCP complex. The O. oeni genome does not encode orthologs of these adapter proteins and the regulation of CtsR activity remains unknown. In this study, we investigate CtsR function in O. oeni by using antisense RNA silencing in vivo to modulate ctsR gene expression. Inhibition of ctsR gene expression by asRNA leads to a significant loss in cultivability after heat shock (58%) and acid shock (59%) highlighting the key role of CtsR in the O. oeni stress response. Regulation of CtsR activity was studied using a heterologous expression system to demonstrate that O. oeni CtsR controls expression and stress induction of the O. oeni hsp18 gene when produced in a ctsR-deficient B. subtilis strain. Under heat stress conditions, O. oeni CtsR acts as a temperature sensor and is inactivated at growth temperatures above 33°C. Finally, using an E. coli bacterial two-hybrid system, we showed that CtsR and ClpL1 interact, suggesting a key role for ClpL1 in controlling CtsR activity in O. oeni.